2008
DOI: 10.3732/ajb.0800199
|View full text |Cite
|
Sign up to set email alerts
|

Towards unlocking the deep nodes of Leguminosae: Floral development and morphology of the enigmatic Duparquetia orchidacea (Leguminosae, Caesalpinioideae)

Abstract: Duparquetia orchidacea (Caesalpinioideae-Cassieae-Duparquetiinae) is a monotypic liana from tropical West Africa. Its highly unusual, zygomorphic flowers, the unique pollen morphology, and the lack of vestured pits in the wood correspond with previous phylogenetic studies that resolved the position of the species to an isolated position among the early-branching Leguminosae. Here we present a detailed analysis of floral morphology and development to clarify open questions of its floral organization. We provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 76 publications
1
31
0
5
Order By: Relevance
“…A strikingly similar pattern was found in the early-branching Duparquetia orchidacea, which also forms only four sepals and in which the first two sepals enlarge considerably and sepals 3 and 4 are formed in short succession in transverse position (Prenner and Klitgaard, 2008). Here too, Prenner and Klitgaard (2008) concluded that there was not enough meristem left for the formation of a fifth sepal primordium.…”
Section: Loss Of the Fifth Sepal Due To Long Plastochronsmentioning
confidence: 56%
See 4 more Smart Citations
“…A strikingly similar pattern was found in the early-branching Duparquetia orchidacea, which also forms only four sepals and in which the first two sepals enlarge considerably and sepals 3 and 4 are formed in short succession in transverse position (Prenner and Klitgaard, 2008). Here too, Prenner and Klitgaard (2008) concluded that there was not enough meristem left for the formation of a fifth sepal primordium.…”
Section: Loss Of the Fifth Sepal Due To Long Plastochronsmentioning
confidence: 56%
“…Here too, Prenner and Klitgaard (2008) concluded that there was not enough meristem left for the formation of a fifth sepal primordium. In contrast to this similarity in the sepal whorl, petal and stamen formation varies considerably among the two species (in Duparquetia petal formation is almost simultaneous, petal aestivation is cochlear descending and there are only four stamens formed, as shown by Prenner and Klitgaard, 2008).…”
Section: Loss Of the Fifth Sepal Due To Long Plastochronsmentioning
confidence: 99%
See 3 more Smart Citations